Water-based-foam-aerosol three-phase synergistic trigger-type fire extinguishing agent and preparation method thereof

CN122937449APending Publication Date: 2026-10-20SHANDONG JINXIANGYING INTERNET OF THINGS TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611116750.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

这一矛盾的本质在于:固体颗粒吸附于气液界面虽能增强液膜强度,但颗粒本身的重力作用和界面排挤效应同时抑制了气泡的生成与膨胀,两者难以兼顾

Benefits of technology

(1)本发明通过热膨胀微球的添加,实现了发泡过程的触发式响应。常温储存时发泡剂被完全封闭;遇火时包覆层软化释放发泡剂,产生大量气体快速发泡。该触发式设计打破了三相泡沫中固体颗粒抑制发泡的固有制约,使灭火剂在发泡瞬间即形成气泡-颗粒复合体,兼顾高发泡倍数与长析液时间。膨胀后的微球兼具物理发泡与隔热屏障双重功能,使灭火剂在泡沫覆盖灭火之外,还具备膨胀微球自身的热阻隔辅助效应,形成水基冷却、泡沫覆盖与物理隔热的三重灭火作用,灭火效率优于单一机制灭火剂。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent and its preparation method, relating to the field of fire extinguishing agent technology. The fire extinguishing agent comprises deionized water, sodium carboxymethyl cellulose, thermally expandable microspheres, composite foam-stabilizing microparticles, sodium dodecyl sulfate, cocamidopropyl betaine, diethylene glycol monobutyl ether, ethylene glycol, urea, and a composite crosslinking agent. This invention utilizes a triple synergistic mechanism of heat-sensitive triggering foaming, pH-responsive foam stabilization, and in-situ gelation anchoring to enable the fire extinguishing agent to possess high foaming ratio, long separation time, rapid fire extinguishing, and excellent storage stability, making it suitable for fighting oil fires.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fire extinguishing agent technology, specifically to a water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent. Background Technology

[0002] Aqueous film-forming foam (AFFF) extinguishing agents are currently the mainstream extinguishing agents for oil fires due to their rapid spreading speed and high extinguishing efficiency. However, traditional AFFF extinguishing agents are gas-liquid two-phase systems, and the thermodynamic instability of the foam leads to rapid liquid separation at high-temperature oil surfaces and poor resistance to reignition. To address these issues, existing technologies introduce solid particles into the foam system to form a three-phase foam. The adsorption of these particles on the bubble-liquid film delays liquid separation and improves foam stability. For example, patent CN110448852A discloses a three-phase foam for extinguishing oil fires, adding fly ash, silica, or zinc oxide particles to the AFFF extinguishing agent, utilizing particle adsorption at the gas-liquid interface to enhance foam stability. Patent CN116236743A further adds alumina particles as a foam stabilizer to the foam extinguishing agent, extending the 25% liquid separation time with increasing particle concentration.

[0003] However, existing three-phase foam extinguishing agents still face the following technical challenges. First, while the addition of solid particles can prolong the liquid release time, it inevitably inhibits foaming performance. Studies show that when the amount of alumina particles added reaches 25g / 100mL, the expansion ratio of environmentally friendly foam extinguishing agents decreases from 9 times to 2.4 times, a reduction of over 70%. This significant decrease in expansion ratio means a substantial reduction in the foam coverage area produced by the same volume of foam liquid, directly affecting the spreading and covering ability and extinguishing efficiency of the extinguishing agent. The essence of this contradiction lies in the fact that while the adsorption of solid particles at the gas-liquid interface can enhance the liquid film strength, the gravity of the particles themselves and the interfacial displacement effect simultaneously inhibit bubble generation and expansion, making it difficult to achieve both simultaneously. Second, existing foam-stabilizing particles are mostly inert inorganic materials, only delaying liquid release through physical adsorption, lacking an active response mechanism. Its foam-stabilizing effect relies on the passive adsorption of particles on the bubble surface. Once the foam spreads on the oil surface and encounters local high temperature or flame impact, the adsorption layer is easily destroyed, and the foam breaks down rapidly, unable to provide continuous foam stabilizing support at different stages of fire development. In other words, the foam-stabilizing effect of existing three-phase foam is a one-time passive defense, lacking the ability to dynamically adjust the foam-stabilizing strength according to environmental stimuli.

[0004] Third, in existing foam extinguishing agents, the foaming and foam-stabilizing functions are performed independently by different components, lacking functional coupling. The foaming agent is responsible for generating bubbles, while the solid particles are responsible for stabilizing them; however, their adsorption at the gas-liquid interface is competitive. The foaming agent molecules reduce surface tension to promote bubble generation, while the particles occupy the interface to enhance the liquid film strength. However, the presence of particles also reduces the effective adsorption area of ​​the foaming agent molecules, leading to a decrease in foaming efficiency. This functionally fragmented design means that foaming and foam stabilization are always in a state of mutual restraint. Fourth, the solid particles in existing three-phase foam extinguishing agents have poor dispersion stability and are prone to sedimentation during storage and transportation, affecting product uniformity and performance. Although some patents use thickeners such as xanthan gum and polyacrylamide to increase the system viscosity and slow sedimentation, these thickeners also increase the viscosity of the foam liquid, hindering its rapid spread on the oil surface and further weakening its extinguishing performance.

[0005] To address the aforementioned issues, this invention proposes a water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent. Through a triple-combination mechanism of heat-sensitive triggering foaming, pH-responsive foam stabilization, and in-situ gelation anchoring, it achieves synergistic triggering and dynamic matching of foaming, foam stabilization, and fire extinguishing functions, overcoming the technical contradiction of mutual restriction between foaming and foam stabilization performance in existing three-phase foams. Summary of the Invention

[0006] The purpose of this invention is to provide a water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent and its preparation method, so as to solve the problems mentioned in the background art.

[0007] In a first aspect, the present invention provides a water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent, comprising the following raw materials by weight: 55-75 parts deionized water; 1-3 parts sodium carboxymethyl cellulose; 0.6-2 parts of glycidyl methacrylate; 6-12 parts of thermally expandable microspheres; 2-4 parts of composite foam-stabilizing microparticles; 3-5 parts sodium dodecyl sulfate; 4-7 parts of cocamidopropyl betaine; 4-7 parts of diethylene glycol monobutyl ether; 5-9 parts of ethylene glycol 3-5 parts urea; 1.5-3 parts of composite crosslinking agent.

[0008] As a preferred embodiment of the present invention, the sodium carboxymethyl cellulose has a degree of substitution of 0.9-1.5 and a viscosity of 1% by mass in an aqueous solution at 25°C of 1% is 1000-2000 mPa·s.

[0009] As a preferred embodiment of the present invention, the method for preparing the composite foam-stabilizing microparticles is as follows: By weight, nano-silica is dispersed in an ethanol-water mixed solvent and ultrasonically dispersed for 20-40 min; 3-aminopropyltriethoxysilane is added, and the pH is adjusted to 4-5 with dilute hydrochloric acid. The mixture is stirred at 50-70℃ for 3-5 h, and after centrifugation, washing, and drying, modified silica is obtained; nano-alumina is dispersed in anhydrous ethanol and ultrasonically dispersed for 15-30 min; stearic acid is added, and the mixture is stirred at 60-80℃ for 3-5 h. After centrifugation, washing, and drying, modified alumina is obtained; the modified silica and modified alumina are mixed and stirred at 400-600 r / min for 20-40 min to obtain the final product.

[0010] As a preferred embodiment of the present invention, the mass ratio of the nano-silica, 3-aminopropyltriethoxysilane and the ethanol-water mixed solvent is (15-25):(0.8-1.5):(80-120), and the volume ratio of ethanol to water in the ethanol-water mixed solvent is (3-5):1.

[0011] As a preferred embodiment of the present invention, the mass ratio of nano-alumina, stearic acid and anhydrous ethanol is (8-12):(1-2):(60-100).

[0012] As a preferred embodiment of the present invention, the mass ratio of modified silica to modified alumina is (1.5-2.5):1.

[0013] As a preferred embodiment of the present invention, the average particle size of the nano-silica is 20-40 nm, and the average particle size of the nano-alumina is 40-60 nm.

[0014] As a preferred embodiment of the present invention, the preparation method of the composite crosslinking agent is as follows: By weight, ammonium persulfate, sodium tetraborate, and N,N'-methylenediacrylamide are dissolved in deionized water and stirred at room temperature for 15-30 minutes until completely dissolved; the resulting solution is freeze-dried and ground through an 80-120 mesh sieve to obtain the final product.

[0015] As a preferred embodiment of the present invention, the mass ratio of ammonium persulfate, sodium tetraborate and N,N'-methylenediacrylamide is (1-2):(1.5-2.5):(0.5-1.5).

[0016] As a preferred embodiment of the present invention, the freeze-drying temperature is -60 to -40°C, the pressure is 5-15 Pa, and the drying time is 20-30 h.

[0017] As a preferred embodiment of the present invention, the mass ratio of sodium dodecyl sulfate to cocamidopropyl betaine is (0.5-1.2):1.

[0018] As a preferred embodiment of the present invention, the thermally expandable microspheres have a thermoplastic polymer (such as polyacrylonitrile copolymer or polymethyl methacrylate copolymer) as the outer shell and are internally encapsulated with a low-boiling-point hydrocarbon foaming agent (such as isobutane or isopentane) as the foaming core.

[0019] It should be noted that this invention uses commercially available thermally expandable microspheres as the triggering foaming component. The thermally expandable microspheres have a thermoplastic polymer (such as polyacrylonitrile copolymer or polymethyl methacrylate copolymer) as the outer shell, and encapsulate a low-boiling-point hydrocarbon foaming agent (such as isobutane or isopentane) as the foaming core. The initial expansion temperature of the thermally expandable microspheres matches the thermal crosslinking temperature window of the sodium carboxymethyl cellulose / glycidyl methacrylate graft in the formulation of this invention. At room temperature, the outer shell is in a glassy state, forming a rigid seal around the core, ensuring that the extinguishing agent does not foam prematurely during storage and maintaining good storage stability. When the extinguishing agent comes into contact with a flame or a hot oil surface, the temperature exceeds the glass transition temperature of polymethyl methacrylate (approximately 105-110°C), the outer shell changes from a glassy state to a highly elastic state, and the internal low-boiling-point hydrocarbons rapidly vaporize, generating internal pressure and causing the microspheres to expand instantaneously. This expansion process generates shear force within the liquid film, which, together with agitation or the introduction of air by injection, promotes the rapid formation of a dense foam layer by the extinguishing agent. Unlike traditional chemical foaming agents, this physical expansion process does not rely on chemical reactions and does not produce additional gas components. All foaming gas is provided by the microsphere core, resulting in strong controllability of the foaming ratio and avoiding the potential damage to foam stability caused by chemical foaming agent residues.

[0020] It should be noted that this invention uses composite foam-stabilizing microparticles as the three-phase foam-stabilizing component. Bubbles generated by the thermal decomposition of thermally expanded microspheres are immediately adsorbed and encapsulated by the composite microparticles, forming a bubble-particle composite. The dual-modal surface structure of these composite microparticles has high adsorption energy for the bubble-liquid film, causing the particles to irreversibly anchor at the gas-liquid interface, forming a particle armor layer on the bubble surface. This armor layer enhances the mechanical strength of the liquid film through the wedge effect of the solid particles, and the accumulation and blocking effect of the particles at the Prandtl boundary layer delays liquid film separation. Compared with traditional single inorganic particles, 3-aminopropyltriethoxysilane-modified silica carries amino groups on its surface, and stearic acid-modified alumina carries carboxyl groups. Under weakly acidic conditions, the difference in surface charge between the two forms electrostatic attraction, resulting in a more dense and ordered arrangement of the composite microparticles at the gas-liquid interface, and a significantly higher foam-stabilizing efficiency than single particles or simple mixed particles.

[0021] It should be further explained that the composite foam-stabilizing microparticles exhibit pH-responsive characteristics. When the extinguishing agent comes into contact with acidic gases produced by flame combustion, the pH of the liquid phase changes, and the amino and carboxyl groups on the surface of the composite microparticles undergo protonation or deprotonation. This results in a reversible change in the charge state and hydrophilicity-hydrophobicity balance of the particle surface, prompting the particles to migrate from the liquid phase to the gas-liquid interface and rearrange themselves, thereby adaptively adjusting the foam-stabilizing intensity according to the fire environment. This response mechanism upgrades the foam-stabilizing effect from static physical adsorption to dynamic environmental adaptation, overcoming the shortcomings of existing three-phase foam stabilizing particles, which are characterized by passive adsorption and lack of regulatory capacity.

[0022] It should be further explained that this invention uses a composite crosslinking agent and sodium carboxymethyl cellulose to form an in-situ gelation system. Ammonium persulfate is stable at room temperature but decomposes at high temperatures to generate free radicals. These free radicals initiate free radical copolymerization crosslinking of the carbon-carbon double bonds grafted onto the sodium carboxymethyl cellulose molecular chain modified with glycidyl methacrylate, forming an irreversible chemical crosslinking network together with N,N'-methylenediacrylamide. Sodium tetraborate dissociates in water to release borate ions, which undergo a condensation reaction with the hydroxyl groups on the sodium carboxymethyl cellulose molecular chain to form borate ester bonds, constituting a reversible physical crosslinking network. N,N'-methylenediacrylamide, under free radical initiation, copolymerizes and crosslinks with the carbon-carbon double bonds grafted onto the sodium carboxymethyl cellulose molecular chain, interpenetrating with the borate ester physical crosslinking network formed by sodium tetraborate, thus constituting a dual-network gel framework with synergistic chemical and physical crosslinking. This gel framework anchors the composite foam-stabilizing microparticles in the foam liquid film, inhibiting particle sedimentation and migration, while significantly improving the viscoelasticity and rupture resistance of the liquid film.

[0023] A second aspect of the present invention provides a method for preparing a water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent, comprising the following steps: S1. Add the prescribed amount of deionized water and sodium carboxymethyl cellulose to a dispersion vessel, and stir at 300-600 r / min for 20-40 min to completely dissolve the sodium carboxymethyl cellulose; add the prescribed amount of glycidyl methacrylate, heat to 60-80℃, and stir at 400-600 r / min for 1-2 h to graft carbon-carbon double bonds onto the sodium carboxymethyl cellulose molecular chain to obtain a thickened aqueous phase; S2. Add the formulated amounts of sodium dodecyl sulfate, cocamidopropyl betaine, diethylene glycol monobutyl ether, ethylene glycol and urea to the thickened aqueous phase obtained in S1, and stir at 400-800 r / min for 15-30 min to obtain mixture A. S3. Add the formulated amounts of thermally expanding microspheres, composite foam-stabilizing microparticles, and composite crosslinking agent to the mixture A obtained in S2. Stir at 600-1000 r / min for 20-40 min until uniformly dispersed. Filter and degas to obtain a water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent.

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention achieves a triggered response in the foaming process by adding thermally expandable microspheres. The foaming agent is completely sealed during room temperature storage; upon contact with fire, the coating softens and releases the foaming agent, generating a large amount of gas for rapid foaming. This triggered design breaks the inherent constraint of solid particles inhibiting foaming in three-phase foam, allowing the extinguishing agent to form a bubble-particle composite at the moment of foaming, balancing high foaming ratio with long liquid separation time. The expanded microspheres possess both physical foaming and thermal insulation functions, enabling the extinguishing agent to not only extinguish fire by covering it with foam but also to have the thermal barrier effect of the expanded microspheres themselves, forming a triple extinguishing effect of water-based cooling, foam coverage, and physical insulation, resulting in extinguishing efficiency superior to single-mechanism extinguishing agents.

[0025] (2) This invention utilizes the design of 3-aminopropyltriethoxysilane-modified silica and composite foam-stabilizing microparticles to form an electrostatic attraction-enhanced arrangement based on the surface charge difference between the two particles, resulting in a higher foam stabilization efficiency than single particles. The composite microparticles also possess pH-responsive characteristics, allowing them to adaptively adjust interfacial adsorption behavior according to the concentration of acidic gases in the fire area, thereby achieving dynamic matching of foam stabilization strength.

[0026] (3) The present invention uses a composite crosslinking agent and a double bond modified sodium carboxymethyl cellulose in situ gelation crosslinking system to form a dual network gel skeleton with chemical crosslinking and physical crosslinking synergy under high temperature triggering, which anchors the foam-stabilizing particles in the foam liquid film, significantly delays the precipitation and inhibits particle sedimentation, and solves the problem of poor storage stability of existing three-phase foam. Detailed Implementation

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] Preparation Example 1 The preparation steps of composite foam-stabilizing microparticles are as follows: By weight, 20 parts of nano-silica were dispersed in 100 parts of an ethanol-water mixed solvent, with a volume ratio of ethanol to water of 4:1. The dispersion was ultrasonically performed (40 kHz, 200 W) for 30 min. One part of 3-aminopropyltriethoxysilane was added, and the pH was adjusted to 4.5 with 0.1 mol / L dilute hydrochloric acid. The mixture was stirred in a 60℃ water bath for 4 h. After the reaction, the mixture was centrifuged at 8000 r / min for 15 min, the supernatant was discarded, and the precipitate was washed three times with anhydrous ethanol and vacuum dried at 80℃ for 12 h to obtain modified silica. 10 parts of nano-alumina were dispersed in 80 parts of anhydrous ethanol and ultrasonically dispersed (40 kHz, 200 W) for 30 min. Add 1.5 parts of stearic acid to W)20 min, stir and react in a 70℃ water bath for 4 h. After the reaction is complete, centrifuge at 8000 r / min for 15 min, discard the supernatant, wash the precipitate three times with anhydrous ethanol, and dry it under vacuum at 70℃ for 12 h to obtain modified alumina; mix modified silica and modified alumina at a mass ratio of 2:1, stir at 500 r / min for 30 min to obtain the final product.

[0029] Preparation Example 2 The preparation steps of the composite crosslinking agent are as follows: By weight, 1.5 parts ammonium persulfate, 2 parts sodium tetraborate and 1 part N,N'-methylenediacrylamide were dissolved in 15 parts deionized water and stirred at room temperature for 20 minutes until completely dissolved. The resulting solution was placed in a freeze dryer and freeze-dried at -50℃ and 10Pa for 24 hours. The white loose powder was collected, ground and passed through a 100-mesh sieve to obtain the final product. Example

[0030] A water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent, comprising the following raw materials by weight: 65 parts deionized water; 1.3 parts glycidyl methacrylate; 2 parts sodium carboxymethyl cellulose; 9 parts thermally expanded microspheres; 3 parts composite foam-stabilizing microparticles prepared in Preparation Example 1; 4 parts sodium dodecyl sulfate; 5.5 parts cocamidopropyl betaine; 5.5 parts diethylene glycol monobutyl ether; 7 parts ethylene glycol; 4 parts urea; 2.3 parts composite crosslinking agent prepared in Preparation Example 2; The thermal expansion microspheres are Nourion's Expancel® 051 DET 40 (initial expansion temperature approximately 106-110°C).

[0031] The degree of substitution of sodium carboxymethyl cellulose is 1.2, and its viscosity in a 1% aqueous solution at 25°C is 1500 mPa·s.

[0032] A method for preparing a water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent is as follows: S1. Add the prescribed amount of deionized water and sodium carboxymethyl cellulose to a dispersion vessel and stir at 450 r / min for 30 min to completely dissolve the sodium carboxymethyl cellulose. Add the prescribed amount of glycidyl methacrylate, heat to 70℃, and stir at 500 r / min for 1.5 h to graft carbon-carbon double bonds onto the sodium carboxymethyl cellulose molecular chain to obtain a thickened aqueous phase. S2. Add the formulated amounts of sodium dodecyl sulfate, cocamidopropyl betaine, diethylene glycol monobutyl ether, ethylene glycol and urea to the thickened aqueous phase obtained in S1, and stir at 600 r / min for 20 min to obtain mixture A. S3. Add the formulated amount of thermally expanded microspheres, the composite foam-stabilizing microparticles prepared in Preparation Example 1, and the composite crosslinking agent prepared in Preparation Example 2 to the mixture A obtained in S2. Stir at 800 r / min for 30 min until uniformly dispersed. Filter through a 200-mesh sieve and degas under vacuum at -0.095 MPa for 15 min to obtain a water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent. Example

[0033] The difference between this embodiment and Example 1 is that the weight parts of the raw materials are adjusted as follows: 55 parts of deionized water, 1 part of sodium carboxymethyl cellulose, 0.6 parts of glycidyl methacrylate, 6 parts of thermally expanded microspheres, 2 parts of the composite foam-stabilizing microparticles obtained in Preparation Example 1, 3 parts of sodium dodecyl sulfate, 4 parts of cocamidopropyl betaine, 4 parts of diethylene glycol monobutyl ether, 5 parts of ethylene glycol, 3 parts of urea, and 1.5 parts of the composite crosslinking agent obtained in Preparation Example 2.

[0034] A method for preparing a water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent is as follows: S1. Add the prescribed amount of deionized water and sodium carboxymethyl cellulose to a dispersion vessel and stir at 300 r / min for 20 min to completely dissolve the sodium carboxymethyl cellulose; add the prescribed amount of glycidyl methacrylate, heat to 60℃, and stir at 400 r / min for 1 h to graft carbon-carbon double bonds onto the sodium carboxymethyl cellulose molecular chain to obtain a thickened aqueous phase; S2. Add the formulated amounts of sodium dodecyl sulfate, cocamidopropyl betaine, diethylene glycol monobutyl ether, ethylene glycol and urea to the thickened aqueous phase obtained in S1, and stir at 400 r / min for 15 min to obtain mixture A. S3. Add the formulated amount of thermally expanded microspheres, the composite foam-stabilizing microparticles prepared in Preparation Example 1, and the composite crosslinking agent prepared in Preparation Example 2 to the mixture A obtained in S2. Stir at 600 r / min for 20 min until uniformly dispersed. Filter through a 200-mesh sieve and degas under vacuum at -0.095 MPa for 15 min to obtain a water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent. Example

[0035] The difference between this embodiment and Example 1 is that the weight parts of the raw materials are adjusted as follows: 75 parts of deionized water, 3 parts of sodium carboxymethyl cellulose, 2 parts of glycidyl methacrylate, 12 parts of thermally expanded microspheres, 4 parts of the composite foam-stabilizing microparticles obtained in Preparation Example 1, 5 parts of sodium dodecyl sulfate, 7 parts of cocamidopropyl betaine, 7 parts of diethylene glycol monobutyl ether, 9 parts of ethylene glycol, 5 parts of urea, and 3 parts of the composite crosslinking agent obtained in Preparation Example 2.

[0036] A method for preparing a water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent is as follows: S1. Add the prescribed amount of deionized water and sodium carboxymethyl cellulose to a dispersion vessel and stir at 600 r / min for 40 min to completely dissolve the sodium carboxymethyl cellulose. Add the prescribed amount of glycidyl methacrylate, heat to 80℃, and stir at 600 r / min for 2 h to graft carbon-carbon double bonds onto the sodium carboxymethyl cellulose molecular chain to obtain a thickened aqueous phase. S2. Add the formulated amounts of sodium dodecyl sulfate, cocamidopropyl betaine, diethylene glycol monobutyl ether, ethylene glycol and urea to the thickened aqueous phase obtained in S1, and stir at 800 r / min for 30 min to obtain mixture A. S3. Add the formulated amounts of the thermally expanded microspheres prepared in Preparation Example 1, the composite foam-stabilizing microparticles prepared in Preparation Example 2, and the composite crosslinking agent prepared in Preparation Example 3 to the mixture A obtained in S2. Stir at 1000 r / min for 40 min until uniformly dispersed. Filter through a 200-mesh sieve and degas under a vacuum of -0.095 MPa for 15 min to obtain a water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent.

[0037] Comparative Example 1 The difference between this comparative example and Example 1 is that the thermally expandable microspheres prepared in Example 1 were not added; instead, an equal part by weight of sodium bicarbonate was added. All other raw material types and amounts, and preparation methods are the same as in Example 1.

[0038] Comparative Example 2 The difference between this comparative example and Example 1 is that the composite foam-stabilizing microparticles obtained in Preparation Example 2 were not added. Instead, an equal weight mixture of unmodified nano-silica and nano-alumina was added (the mass ratio of nano-silica to nano-alumina was the same as in Preparation Example 2, which was 2:1). The other types and amounts of raw materials and the preparation methods were the same as in Example 1.

[0039] Comparative Example 3 The difference between this comparative example and Example 1 is that the composite crosslinking agent prepared in Preparation Example 3 was not added. All other raw material types and amounts, and preparation methods are the same as in Example 1.

[0040] Comparative Example 4 The difference between this comparative example and Example 1 is that sodium carboxymethyl cellulose, the composite crosslinking agent obtained in Preparation Example 3, and glycidyl methacrylate were not added; instead, an equal part by weight of xanthan gum was added. All other raw materials, amounts, and preparation methods are the same as in Example 1.

[0041] test: I. Foaming Performance Test Refer to the method for determining the expansion ratio in GB / T 15308-2006 Foam Extinguishing Agents. Dilute the extinguishing agent samples prepared in Examples 1-3 and Comparative Examples 1-4 to 6% (volume fraction) with deionized water. Take 100 mL of the diluted solution and add it to a graduated cylinder. Stir with a DJ1C-100 electric stirrer at 1000 r / min for 60 s, and immediately record the total foam volume V1. Calculate the expansion ratio using the following formula: Expansion ratio = V1 / 100 Each group of samples was tested 3 times, and the arithmetic mean was taken.

[0042] II. 25% precipitation time test Refer to the 25% separation time determination method in GB / T 15308-2006. Immediately fill a 100mL stoppered graduated cylinder with the foam immediately after stirring and foaming as described in the foaming performance test, record the initial foam height, collect the separated liquid at the bottom of the graduated cylinder, and record the time when the volume of separated liquid reaches 25% of the initial foam volume, which is the 25% separation time. Test each group of samples three times and take the arithmetic mean.

[0043] III. Thermally Triggered Foaming Temperature Test Take 50 mL of each of the fire extinguishing agent samples prepared in Examples 1-3 and Comparative Example 1, and place them in 100 mL beakers. Heat them from 25 °C to 200 °C at a heating rate of 2 °C / min. Record the temperature at which the sample begins to expand and foam significantly, which is the thermally triggered foaming temperature.

[0044] IV. Fire Extinguishing Performance Test The extinguishing performance test method for Class B fires was performed according to GB / T 15308-2006. A standard oil pan with a diameter of 1.48m was used. A 20mm thick layer of water was laid at the bottom of the oil pan, and then 20L of 93-octane gasoline was added. The gasoline in the oil pan was ignited and pre-burned for 60 seconds. The extinguishing agent samples prepared in Examples 1-3 and Comparative Examples 1-4 were filled into a portable fire extinguisher (filling pressure 1.2MPa, with a negative pressure suction foaming device at the outlet). The extinguishing agent spray flow rate was 0.5L / s. During spraying, the foam entered tangentially along the oil pan, and the time from the start of spraying to the complete extinguishing of the flame was recorded as the extinguishing time. Each group of samples was tested 3 times, and the arithmetic mean was taken.

[0045] V. Fire Resistance Test Refer to the method for determining the fire resistance time in GB / T 15308-2006. After completing the fire extinguishing performance test, wait until the foam layer completely covers the oil surface, place a stainless steel cylinder with a diameter of 10 cm in the center of the oil pan, add 100 mL of 93-octane gasoline into the cylinder and ignite it, and record the time from the time the gasoline in the cylinder is ignited until the foam layer in the oil pan is destroyed and the gasoline in the oil pan is ignited. This time is the fire resistance time.

[0046] VI. Storage Stability Test Take 500 mL of each of the fire extinguishing agent samples prepared in Examples 1-3 and Comparative Examples 1-4, and place them in sealed polyethylene bottles. Store them at room temperature (25±2℃) for 180 days. Before storage and after 180 days of storage, take 50 mL of the upper and lower layer liquids respectively, and determine the foaming ratio according to the foaming performance test method described above. Calculate the foaming ratio retention rate using the following formula: Foaming ratio retention rate (%) = (Foaming ratio of the lower layer after 180 days of storage / Foaming ratio before storage) × 100% At the same time, observe whether the sample shows stratification, precipitation or flocculation after 180 days of storage.

[0047] VII. Summary of Results Table 1: Test Results of Foaming Performance, Liquid Separation Time and Thermal Trigger Temperature Example 1 7.4 28.5 108 Example 2 7.3 30.1 106 Example 3 7.6 26.7 110 Comparative Example 1 5.4 16.2 82 Comparative Example 2 6.4 14.8 109 Comparative Example 3 6.7 13.2 105 Comparative Example 4 6.9 8.6 110 Table 2: Test Results of Fire Extinguishing Performance and Burn Resistance Example 1 43 17.4 Example 2 40 18.2 Example 3 45 16.8 Comparative Example 1 58 11.4 Comparative Example 2 55 10.8 Comparative Example 3 62 9.6 Comparative Example 4 71 7.3 Table 3: Test Results of Fire Extinguishing Performance and Burn Resistance Example 1 7.4 6.9 93.2 Uniform and without layering Example 2 7.3 6.7 91.8 Uniform and without layering Example 3 7.6 7.0 92.1 Uniform and without layering Comparative Example 1 5.4 2.6 48.1 There is obvious stratification, with sediment in the lower layer. Comparative Example 2 6.4 4.6 71.9 Slight stratification Comparative Example 3 6.7 5.2 77.6 Slight stratification Comparative Example 4 6.9 3.9 56.5 Clear stratification, with a large amount of sediment. VIII. Discussion of Results As shown in Tables 1-3, the water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent prepared in Examples 1-3 of this invention has excellent foaming performance, foam stability, fire extinguishing performance, anti-burning performance and storage stability.

[0048] Regarding foaming performance and drainage time, Examples 1-3 showed significantly better foaming ratios and 25% drainage times than the Comparative Example. Comparative Example 1, due to the use of uncoated sodium bicarbonate instead of thermally expanded microspheres, exhibited significantly lower foaming ratios and drainage times compared to the Examples. This is because sodium bicarbonate undergoes partial slow decomposition during the preparation and storage of the extinguishing agent, resulting in a loss of effective foaming components and a decrease in foaming capacity. Simultaneously, the gas generated by the decomposition of sodium bicarbonate is released in a diffuse manner, failing to form a bubble-particle complex with the composite foam-stabilizing microparticles at the moment of bubble formation. Consequently, the foam-stabilizing effect of the particles was not fully realized, and the drainage time was significantly shortened. These results indicate that the effective protection of the foaming agent by the outer shell coating of the thermally expanded microspheres is crucial to ensuring that the foaming agent does not deactivate during storage and foams sufficiently during use. Comparative Example 2, using an unmodified mixture of nano-silica and nano-alumina instead of the composite foam-stabilizing microparticles, achieved a foaming ratio comparable to the Examples, but with a significantly shorter drainage time. This is because the surface of unmodified inorganic particles lacks amino and carboxyl functional groups, making it impossible for particles to form an electrostatically enhanced ordered arrangement. This results in low adsorption energy at the gas-liquid interface, making it difficult to form a dense particle armor layer and significantly reducing foam stabilization. Comparative Example 3, without the addition of the composite crosslinking agent, showed a significantly shorter separation time than the example, demonstrating that the gel framework triggered by the composite crosslinking agent plays an irreplaceable role in anchoring particles and delaying separation. Replacing sodium carboxymethyl cellulose, glycidyl methacrylate, and the composite crosslinking agent with xanthan gum, although the foaming ratio before storage was similar to the example, resulted in the shortest separation time among all samples. This further verifies that the thickening effect of sodium carboxymethyl cellulose, the double-bond crosslinking sites provided by glycidyl methacrylate, and the crosslinking effect of the composite crosslinking agent are all indispensable. Physical thickening by xanthan gum alone cannot form a dual-network gel framework with the synergistic effect of chemical and physical crosslinking, thus failing to effectively delay separation.

[0049] Regarding the thermally triggered foaming temperature, the thermally triggered foaming temperatures of Examples 1-3 are consistent with the glass transition temperature of polymethyl methacrylate, demonstrating that the softening release of the coating layer is the controlling step in triggering foaming. The thermally triggered foaming temperature of Comparative Example 1 is significantly lower than that of the Examples, because the uncoated sodium bicarbonate begins to decompose slowly at lower temperatures, leading to continuous loss of the foaming agent during storage and transportation. These results demonstrate that the outer shell coating of the thermally expanded microspheres effectively increases the decomposition temperature of the foaming agent and significantly improves the storage stability of the fire extinguishing agent.

[0050] In terms of fire extinguishing and fire resistance performance, Examples 1-3 showed significantly better fire extinguishing and fire resistance times than the comparative examples. Comparative Example 1 exhibited worse fire extinguishing and fire resistance times than the examples due to its low foaming ratio, short separation time, and insufficient integrity and durability of the foam layer's coverage on the oil surface. Comparative Example 2 also showed worse fire extinguishing and fire resistance times than the examples; although its foaming ratio was acceptable, its foam stability was poor, failing to form a durable coverage layer on the oil surface. Comparative Example 3 also showed worse fire extinguishing and fire resistance times than the examples, with the lack of a gel skeleton indicating significantly insufficient resistance to flame impact. Comparative Example 4 had the worst fire extinguishing and fire resistance times among all samples, further demonstrating the crucial contribution of the gel skeleton composed of sodium carboxymethyl cellulose, glycidyl methacrylate, and the composite crosslinking agent to foam stability and fire resistance performance.

[0051] Regarding storage stability, after 180 days of static storage at room temperature, the foaming ratio retention rate of the lower layer in Examples 1-3 remained at a high level, and the samples exhibited a uniform appearance without stratification. Comparative Example 1 showed a significantly lower foaming ratio retention rate, with obvious stratification and sedimentation in the lower layer. This was because the uncoated sodium bicarbonate continuously decomposed and was lost during storage, resulting in a continuous decrease in the effective content of the foaming agent and a severe reduction in foaming capacity after storage. Simultaneously, the gas escape process generated by the decomposition of sodium bicarbonate as a foaming agent caused continuous disturbance to the system, disrupting the stable dispersion of particles in the liquid phase and accelerating particle sedimentation. Comparative Example 2 showed a lower foaming ratio retention rate than the examples and exhibited slight stratification, demonstrating that unmodified inorganic particles will undergo some degree of sedimentation during storage. Comparative Example 3 showed a lower foaming ratio retention rate than the examples and exhibited slight stratification, demonstrating that particles lacking gel-based anchoring will still migrate and aggregate during long-term storage. The foaming ratio retention rate of Comparative Example 4 was significantly lower, and the sample showed obvious stratification and a large amount of sediment. This is because after replacing sodium carboxymethyl cellulose, glycidyl methacrylate and composite crosslinking agent with xanthan gum, the system lacked the thickening and suspending effect of sodium carboxymethyl cellulose, the carbon-carbon double bond crosslinking sites provided by glycidyl methacrylate, and the chemical crosslinking network and borate ester physical crosslinking network triggered by the composite crosslinking agent, resulting in the most severe particle sedimentation.

[0052] It should be noted that Comparative Example 2 is similar to the Example in terms of foaming performance, but significantly inferior in terms of foam stability, fire extinguishing performance, and storage stability. This indicates that the surface functional group modification of the composite foam-stabilizing microparticles in this invention is key to achieving efficient foam stabilization; a simple mixture of unmodified particles cannot achieve the same foam stabilization effect. Comparative Example 3 is comparable to the Example in terms of foaming performance, but also significantly inferior in terms of foam stability, fire extinguishing performance, and storage stability. This indicates that the anchoring effect of the gel skeleton on the particles not only affects the immediate stability of the foam but also the fire extinguishing effect and long-term storage performance.

[0053] In summary, the water-based foam-aerosol three-phase synergistic triggered fire extinguishing agent prepared in Examples 1-3 of this invention successfully overcomes the three major technical challenges in the prior art: solid particles inhibiting foaming, lack of dynamic response in foam stabilization, and poor particle storage stability. This is achieved through the triple synergy of the triggered release mechanism of thermally expanded microspheres, the pH-responsive interfacial adsorption mechanism of composite foam-stabilizing microparticles, and the in-situ triple network gelation and anchoring mechanism of composite crosslinking agent and sodium carboxymethyl cellulose. The agent exhibits excellent performance in terms of foaming ratio, foam stability, fire extinguishing efficiency, anti-burning performance, and storage stability, and has good prospects for industrial application.

[0054] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0055] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the scope defined by the invention, and all such modifications and additions should fall within the protection scope of the present invention.

Claims

1. A water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent, characterized in that: Including the following parts by weight of raw materials: 55-75 parts deionized water; 1-3 parts sodium carboxymethyl cellulose; 0.6-2 parts of glycidyl methacrylate; 6-12 parts of thermally expandable microspheres; 2-4 parts of composite foam-stabilizing microparticles; 3-5 parts sodium dodecyl sulfate; 4-7 parts of cocamidopropyl betaine; 4-7 parts of diethylene glycol monobutyl ether; 5-9 parts of ethylene glycol; 3-5 parts urea; 1.5-3 parts of composite crosslinking agent.

2. The water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent according to claim 1, characterized in that: The degree of substitution of the sodium carboxymethyl cellulose is 0.9-1.

5.

3. The water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent according to claim 1, characterized in that: The thermally expandable microspheres have a thermoplastic polymer shell and are encapsulated with a low-boiling-point hydrocarbon foaming agent as a foaming core.

4. The water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent according to claim 1, characterized in that: The preparation method of the composite foam-stabilizing microparticles is as follows: By weight, nano-silica was dispersed in an ethanol-water mixed solvent and ultrasonically dispersed for 20-40 min; 3-aminopropyltriethoxysilane was added, and the pH was adjusted to 4-5 with dilute hydrochloric acid. The mixture was stirred at 50-70℃ for 3-5 h, and after centrifugation, washing, and drying, modified silica was obtained; nano-alumina was dispersed in anhydrous ethanol and ultrasonically dispersed for 15-30 min; stearic acid was added, and the mixture was stirred at 60-80℃ for 3-5 h. After centrifugation, washing, and drying, modified alumina was obtained; The modified silica and modified alumina are mixed and stirred at 400-600 r / min for 20-40 min to obtain the final product.

5. The water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent according to claim 4, characterized in that: The mass ratio of the nano-silica, 3-aminopropyltriethoxysilane and the ethanol-water mixed solvent is (15-25):(0.8-1.5):(80-120), and the volume ratio of ethanol to water in the ethanol-water mixed solvent is (3-5):

1.

6. The water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent according to claim 4, characterized in that: The mass ratio of nano-alumina, stearic acid and anhydrous ethanol is (8-12):(1-2):(60-100); the mass ratio of modified silica to modified alumina is (1.5-2.5):

1.

7. The water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent according to claim 1, characterized in that: The preparation method of the composite crosslinking agent is as follows: By weight, ammonium persulfate, sodium tetraborate, and N,N'-methylenediacrylamide are dissolved in deionized water and stirred at room temperature for 15-30 minutes until completely dissolved; the resulting solution is freeze-dried and ground through an 80-120 mesh sieve to obtain the final product.

8. The water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent according to claim 7, characterized in that: The mass ratio of ammonium persulfate, sodium tetraborate and N,N'-methylenediacrylamide is (1-2):(1.5-2.5):(0.5-1.5); the freeze-drying temperature is -60 to -40°C, the pressure is 5-15 Pa and the drying time is 20-30 h.

9. The water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent according to claim 1, characterized in that: The mass ratio of sodium dodecyl sulfate to cocamidopropyl betaine is (0.5-1.2):

1.

10. A method for preparing a water-based-foam-aerosol three-phase synergistic triggering fire extinguishing agent as described in any one of claims 1-9, characterized in that: Includes the following steps: S1. Add the prescribed amount of deionized water and sodium carboxymethyl cellulose to a dispersion vessel, and stir at 300-600 r / min for 20-40 min to completely dissolve the sodium carboxymethyl cellulose; add the prescribed amount of glycidyl methacrylate, heat to 60-80℃, and stir at 400-600 r / min for 1-2 h to graft carbon-carbon double bonds onto the sodium carboxymethyl cellulose molecular chain to obtain a thickened aqueous phase; S2. Add the formulated amounts of sodium dodecyl sulfate, cocamidopropyl betaine, diethylene glycol monobutyl ether, ethylene glycol and urea to the thickened aqueous phase obtained in S1, and stir at 400-800 r / min for 15-30 min to obtain mixture A. S3. Add the formulated amounts of thermally expanding microspheres, composite foam-stabilizing microparticles, and composite crosslinking agent to the mixture A obtained in S2. Stir at 600-1000 r / min for 20-40 min until uniformly dispersed. Filter and degas to obtain a water-based foam-aerosol three-phase synergistic triggering fire extinguishing agent.

Citation Information

Patent Citations

  • Foam stabilizer for foam fire extinguisher and application of foam stabilizer

    CN116236743A